2020
DOI: 10.1101/2020.01.27.921650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping physiological ADP-ribosylation using Activated Ion Electron Transfer Dissociation (AI-ETD)

Abstract: max. 150 words)ADP-ribosylation (ADPr) is a post-translational modification that plays pivotal roles in a wide range of cellular processes. Mass spectrometry (MS)-based analysis of ADPr under physiological conditions, without relying on genetic or chemical perturbation, has been hindered by technical limitations. Here, we describe the applicability of Activated Ion Electron Transfer Dissociation (AI-ETD) for MS-based proteomics analysis of physiological ADPr using our unbiased Af1521 enrichment strategy. To be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…This led to the notion that the major ADPr acceptor residues are the acidic amino acids, glutamate (Glu) and aspartate (Asp), as well as the basic amino acid arginine (Arg). More recently, however, mass spectrometry-based proteomics has revealed that in addition to Glu/Asp and Arg, serine (Ser), tyrosine (Tyr), histidine (His), and cysteine (Cys) can also act as ADPr acceptors ( Buch-larsen, 2020 ; Larsen et al, 2018 ; Leslie Pedrioli et al, 2018 ; Palazzo et al, 2018 ; Leidecker et al, 2016 ). While many residues can act as ADPr acceptors, a major outstanding question in the field is whether or not individual PARP family members demonstrate selectivity toward ADP-ribosylation of specific residues in protein targets.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the notion that the major ADPr acceptor residues are the acidic amino acids, glutamate (Glu) and aspartate (Asp), as well as the basic amino acid arginine (Arg). More recently, however, mass spectrometry-based proteomics has revealed that in addition to Glu/Asp and Arg, serine (Ser), tyrosine (Tyr), histidine (His), and cysteine (Cys) can also act as ADPr acceptors ( Buch-larsen, 2020 ; Larsen et al, 2018 ; Leslie Pedrioli et al, 2018 ; Palazzo et al, 2018 ; Leidecker et al, 2016 ). While many residues can act as ADPr acceptors, a major outstanding question in the field is whether or not individual PARP family members demonstrate selectivity toward ADP-ribosylation of specific residues in protein targets.…”
Section: Introductionmentioning
confidence: 99%
“…With thousands of sites in the human cell, serine ADP-ribosylation appears to be a major contributor to the proteome complexity. Further promising candidates include cysteine [23,57,60] and tyrosine [23,51,58], which might be the targets of specific PARP family members; several other amino acids are also possible as acceptors. Moreover, it has emerged that PARPs and related ARTs can modify not only proteins, but also nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of PARP1 itself as the main or at least a major PAR acceptor in vivo [19] was followed by the narrowing down of the modification sites to the 'automodification domain', a central region of the polymerase between the DNA-binding and catalytic segments [20]. For reasons that are explained below, PARP1 automodifies in cells at both glutamate/aspartate and serine residues, and major sites include glutamates 488 and 491 [21] and serines 499, 507 and 519 [22,23]. One key function of PARP automodification appears to be to release the enzyme from DNA lesions, presumably through electrostatic and steric repulsion [24][25][26].…”
Section: Short History Of Parp Specificity Researchmentioning
confidence: 99%
See 2 more Smart Citations